Dative constructions in Romance and beyond - Mateu, Jaume; Pineda, Anna (Language Science Press, 2020)
This book offers a comprehensive account of dative structures across languages -with an important, though not exclusive, focus on the Romance family. As is well-known, datives play a central role in a variety of structures, ranging from ditransitive constructions to cliticization of indirect objects and differentially marked direct objects, and including also psychological predicates, possessor or causative constructions, among many others. As interest in all these topics has increased significantly over the past three decades, this volume provides an overdue update on the state of the art. Accordingly, the chapters in this volume account for both widely discussed patterns of dative constructions as well as those that are relatively unknown.
Description based on print version record.
Language Science Press 2018-2020
Keywords: Language Arts & Disciplines / Linguistics; Language arts; Electronic books